2010
DOI: 10.1007/s11829-010-9099-y
|View full text |Cite
|
Sign up to set email alerts
|

Explaining differential herbivory in sun and shade: the case of Aristotelia chilensis saplings

Abstract: Differential herbivory in contrasting environments is commonly explained by differences in plant traits. When several plant traits are considered, separate correlation analyses between herbivory and candidate traits are typically conducted. This makes it difficult to discern which trait best explain the herbivory patterns, or to avoid spurious inferences due to correlated characters. Aristotelia chilensis saplings sustain greater herbivory in shaded environments than in open habitats. We measured alkaloids, ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 45 publications
4
33
0
1
Order By: Relevance
“…In sunny environments the increase in carbon content in plant tissues and the consequent changes in the carbon to nitrogen ratio correlates negatively with the rate of acquisition of nutrients (nitrogen) by herbivores; more leaf tissue has to be consumed to assimilate enough nutrients due to the nitrogen dilution effect (Mattson Jr. 1980). In agreement with our findings it has been reported that herbivory correlates positively with sunlight exposition (Louda & Rodman 1996, Dicke 2000 although the opposite pattern (i.e low herbivory in sunny microhabitats) has also been documented in some systems (Guerra et al 2010;Barber & Marquis 2011). Explanations for the negative relationship between herbivory and sunlight invoke three main issues: 1) Predation rates on herbivores is high in open sites and low in shaded sites.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In sunny environments the increase in carbon content in plant tissues and the consequent changes in the carbon to nitrogen ratio correlates negatively with the rate of acquisition of nutrients (nitrogen) by herbivores; more leaf tissue has to be consumed to assimilate enough nutrients due to the nitrogen dilution effect (Mattson Jr. 1980). In agreement with our findings it has been reported that herbivory correlates positively with sunlight exposition (Louda & Rodman 1996, Dicke 2000 although the opposite pattern (i.e low herbivory in sunny microhabitats) has also been documented in some systems (Guerra et al 2010;Barber & Marquis 2011). Explanations for the negative relationship between herbivory and sunlight invoke three main issues: 1) Predation rates on herbivores is high in open sites and low in shaded sites.…”
Section: Discussionsupporting
confidence: 91%
“…This is also concordant with our observations since we found less herbivory, despite a high abundance of herbivores in the site where leaves had higher content of nutrients. Then, our evidence agree with three of the most likely process that should lead to low levels of herbivory in sunny and warm habitats (Guerra et al 2010, Barber & Marquis 2011. However, it was in the open canopy site where we found higher herbivory as compared with the more shaded site.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies suggest that herbivory tends to be higher on plants grown in shade compared with conspeciÞc plants grown in full sun (Maiorana 1981, Guerra et al 2010. This hypothesis, referred to as the shade habitat hypothesis (Louda et al 1987), has been supported by several studies.…”
mentioning
confidence: 86%
“…October-December 2017 Thicker leaves can hinder the actions of insect herbivores (Corrêa 2007;Hanley et al 2007;Guerra et al 2010) and it was observed in D. viscosa present in forest edges, under higher light intensity. The trade-off between thickness and leaf area was a response to high light incidence in these vegetation types, in order to reduce the transpiration surface (Melo Jr. & Boeger 2016).…”
Section: Maiara Matilde Da Silva Maria Regina Torres Boeger João Camentioning
confidence: 99%